The Management Roles, Leadership Profile, and Training Needs of the Management Staff of the MSU-IIT Employees Multi-Purpose Cooperative: Basis for an Executive Development Program - JALANDONI OREJANA, ANNIE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The study deals with the determination of the extent of management roles, leadership profile, and training needs of the management staff of MSU-IIT Employees Multipurpose Cooperative as perceived by the management staff and the members of the cooperative. The findings reveal that the management roles such as interpersonal roles, informational roles, and decisional roles are performed by the management staff Often or in 76% to 95% of the cases. As a whole the management staff are perceived to practice the consultative style of leadershËp. Moreover, the study disclose that the following are the foremost training needs of the man agement staf: advance determination of what should be accomplished and how it should be realized; goal-setting: grievance procedure; team building and building trust. The outcome of the Fisher's T-test shows that there are no significant dif. jerences between the perception of the management staff and the members of the cooperative regarding the extent of management roles of the management staff. The result also shows that there is no significant difference in the perceived leadership profile of the management staff by the management staff and the members of the cooperative. therefore the null hypothesis are accepted. as shown by the spearman Rho Test if differences in ranking of by thte management staff and those of the members of the cooperarive to the former's training needs.